"I Couldn't Have Learned This Any Other Way": Learning to Teach Literacy across Concurrent Practicum Experiences. (2nd January 2016) - Mosley Wetzel, Melissa; L. Roser, Nancy; Hoffman, James V.; Antonio Martínez, Ramón; Price-Dennis, Detra
ABSTRACT: The authors, a team of literacy teacher educators who are focused on extending our own understandings of preservice teacher (PST) learning, conducted a cross-case analysis of how PSTs learned to teach literacy in three concurrent practicum experiences. We draw on Grossman's framework of representations, decompositions, and approximations to describe and interpret what PSTs learned. Through a focus on one student, Deanna, the authors illustrate three findings: PSTs came to value the variety of forms of students' literacies that reflected their ages, language backgrounds, and cultures/identities; they came to understand that relationships are essential to teaching and learning, and building relationships requires "putting myself out there" as well as "getting to know you"; and coming to know about students' literacies in contexts in which students can talk, read, make images, and write from life allowed PSTs to coconstruct a curriculum that followed the students' leads. The concurrence of practicum experience allowed for deepened reflections and understandings of literacy teaching. To extend Grossman's work, the authors suggest the importance of using artifacts of PSTs' own practices as representations in a cycle of reflection.